Recent Advances in the Design of Structures with Passive Energy Dissipation Systems - Ricciardi, Giuseppe; De Domenico, Dario; Zhang, Ruifu; Ricciardi, Giuseppe; De Domenico, Dario; Zhang, Ruifu (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Passive vibration control plays a crucial role in structural engineering. Common solutions include seismic isolation and damping systems with various kinds of devices, such as viscous, viscoelastic, hysteretic, and friction dampers. These strategies have been widely utilized in engineering practice, and their efficacy has been demonstrated in mitigating damage and preventing the collapse of buildings, bridges, and industrial facilities. However, there is a need for more sophisticated analytical and numerical tools to design structures equipped with optimally configured devices. On the other hand, the family of devices and dissipative elements used for structural protection keeps evolving, because of growing performance demands and new progress achieved in materials science and mechanical engineering. This Special Issue collects 13 contributions related to the development and application of passive vibration control strategies for structures, covering both traditional and innovative devices. In particular, the contributions concern experimental and theoretical investigations of high-efficiency dampers and isolation bearings; optimization of conventional and innovative energy dissipation devices; performance-based and probability-based design of damped structures; application of nonlinear dynamics, random vibration theory, and modern control theory to the design of structures with passive energy dissipation systems; and critical discussion of implemented isolation/damping technologies in significant or emblematic engineering projects.
English
Keywords: History of engineering & technology; stay cable; vibration control; hybrid control; inertial mass damper; viscous damper; passive vibration control; inerter system; cable bracing; parametric study; optimal design; tuned mass damper; inerter; high-rise buildings; wind tunnel test; wind-induced response; structural control; synchronous multi-point pressure measurement; seismic protection; displacement-dependent damping; stochastic dynamic analysis; metal damper; performance parameter; cyclic loading test; hysteretic behavior; energy dissipation capability; multi-degree of freedom; graphical approach; suspension bridges; seismic test; pushover test; precast concrete structure; shake table; Base-Isolated Buildings; bearing displacement; STMD; MTMDs; d-MTMDs; incremental dynamic analysis; earthquake; energy dissipation; (3z(Bdouble-step(3y (Bcharacteristicss; stiffness lifting; seismic performance; horizontal connection; prefabricated shear wall structural systems; high-tech factory; lead rubber bearing; moving crane; soil structure interaction; vibration; wind load; motion-based design; uncertainty conditions; constrained multi-objective optimization; reliability analysis; passive structural control; cable-stayed bridges; adjacent buildings; seismic pounding